Numerical modeling study of the effect of some critical parameters on caving behavior of strata and support performance in a longwall working - Singh G.S.P.; Singh U.K. (My University, 2025)
The observations obtained from numerical modeling based parametric study on the effect of different factors on the caving behavior of strata and load on support with progressive face advance is discussed. The basic data for this parametric study has been obtained by averaging the values compiled from 23 longwall panels extracted in different coal fields of India. For analyzing the characteristics of different layers in roof, overlying the coal seam in all such cases, different rock beds above the coal seam have been identified from detailed logging data of core samples of a representative borehole drilled over the panel. The parametric study shows that installing a stiffer support in deep mining condition may lead to unnecessary loading which can be avoided by selecting a suitable support of lower stiffness as per the basics of support design using ground response curve. An increase in situ horizontal stress in the direction of face advance leads to formation of a larger overhang, which causes en masse caving during main fall in the worst condition.